2017
DOI: 10.1097/rlu.0000000000001491
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Stromal Tumor Showing Intense Tracer Uptake on PSMA PET/CT

Abstract: A 70-year-old man with suspected prostate cancer was referred for Ga-PSMA-HBED-CC PET/CT (short PSMA PET/CT) for staging of tumor extent. Apart from vivid tracer uptake in the prostate gland and osseous metastasis, PSMA PET/CT revealed a large soft tissue mass with calcifications in the left upper abdomen showing intense tracer uptake. Histologic examination revealed the mass to be a gastrointestinal stromal tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In the late 1990s it was found that the neovasculature of many solid tumours also expresses PSMA [13]. Recently, there have been many reports of the uptake of PSMA ligands in various nonprostate tissues [14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1990s it was found that the neovasculature of many solid tumours also expresses PSMA [13]. Recently, there have been many reports of the uptake of PSMA ligands in various nonprostate tissues [14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…PSMA PET imaging improves the detection rates for metastatic lesions in lymph nodes and bone, especially at low prostate-specific antigen levels (14)(15)(16)(17)(18)(19)(20). In addition, favorable imaging properties have also been demonstrated in nonprostate cancers (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Haffner et al [20] Oral cancer Haffner et al [21] gastric and colorectal cancers Wang et al [22] Lung cancer Wernicke et al [23] Breast cancer Wernicke et al [24] Endometrial and ovarian cancer Baccala et al [25] Rhee et al [26] Renal cancer Samplaski et al [27] Bladder cancer Nomura et al [28] Wernicke et al [29] Glioblastoma Kanthan et al [30] Follicular lymphoma Sasikumar et al [31] Brain tumors Sasikumar et al [32] Multiple myeloma Sasikumar et al [33] Hepatocellular carcinoma Sasikumar et al [34] Osteosarcoma Alipour et al [35] Hepatocellular cholangiocarcinoma Anconina et al [36] Melanoma Krishnaraju et al [37] Thymoma type B2 Malik et al [38] GE junction adenocarcinoma Malik et al [39] Signet-ring cell carcinoma Noto et al [40] GI stromal tumor Stoykow et al [41] Rectal adenocarcinoma Vamadevan et al [42] Pancreatic neuroendocrine tumor Arora et al [43] Adrenocortical carcinoma Froehner et al [44] Squamous cell carcinoma of the penis…”
Section: Table 1: Previous Literatures On Prostate-specific Membrane ...mentioning
confidence: 99%